HUBUNGAN ANTARA TINGKAT PENGETAHUAN TENTANG IMPLANT DENGAN PEMAKAIAN KONTRASEPSI IMPLANT PADA AKSEPTOR DI BPS NY. HJ. FAROHAH DESA DUKUN GRESIK - Taqiyyah Barroh Thoyyib; Yunik Windarti (Jurnal Ilmiah Kesehatan, 2014)
The purposed to find out the relationship between the knowledge about implant and implant contraceptive used of acceptors at BPS Farohah Gresik. Implant is one of hormone contraceptive methode with high effectiveness. But, know fact that there were acceptors refused to use implant. The caused factor is the less off acceptors knowledge about implant. Therefore, this research was purposed to find out the relationship between the knowledge about implant and implant contraceptive used of acceptors at BPS Farohah Gresik. The type of this research was analytic by cross sectional methode. The population involved 42 acceptors of hormonal contraceptive who attended on June at BPS Farohah Gresik. 38 respondents were taken as the samples using simple random sampling technique. The independent variable was knowledge where as, the dependent one was the used of implant. Questionnaires was used to collect the data. Analyzed by using Mann-Whitney test with the significance level α = 0,05. The result of this research showed that most of respondents (60,5%) had less knowledge and almost all respondents (89,5%) did not use implant. Furthermore, the statistic test has obtarned p = 0,039 < α = 0,05. So H0 was refused that there was a relationship between knowledge about implant and the used of implant contraceptive at BPS Farohah Gresik. The research concluded that the less of acceptors knowledge about implant. The used of this contraceptive is vower. Hence, the health workers should improve the counselling and implant extension to people.